Harnessing the crosstalk of adipocytes, autophagy, and immune cells for immunotherapy in obesity - G. Guerrero M, Gloria (Trends in Immunotherapy, 2022)
As a self-degradative and recycling program, autophagy plays an essential role in homeostasis and life. The connection between autophagy and the status of the adipose tissue (white or beige/brown) links to metabolic diseases such as obesity, type two diabetes mellitus (T2DM). Moreover, autophagy and the renin-angiotensin physiological system play a pivotal role in metabolic syndrome, a disease that can disrupt homeostasis in different organs, including adipose tissue. The crosstalk in adipose tissue maintains low inflammation, brown adipocytes, and autophagic machinery under control. The JAK-STAT signalization pathway and the paracrine action of hormones, adipokines, and cytokines play a role in maintaining the status of low inflammation, brown adipocytes, and autophagic machinery to harness the utmost for obesity immunotherapy.